2005
DOI: 10.1177/875697280503600205
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Behavioral Competencies of Client-Focused and Production-Focused Project Managers in the Construction Sector

Abstract: The importance of evaluating behaviors as an underpinning component of the project management body of knowledge is widely recognized. This paper reports on research that evaluated the behaviors of two functionally disparate sets of project managers operating within the construction industry. The first comprised those with overall responsibility for the on-site production function (the management contractor), while the second comprised client project managers overseeing project activities on behalf of the procu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 6 publications
1
39
0
3
Order By: Relevance
“…The competencies, often called emotional intelligence (EI), were recognised as leadership competence and are now believed to be a key project management competence (Dulewicz and Higgs, 2000;Müller and Turner, 2007) through a number of recent studies in PM across industry sectors (Turner et al, 2009) and in specific sectors such as defence (Turner and Lloyd-Walker, 2008) and construction (Dainty et al, 2004(Dainty et al, , 2005. EI often encompasses self-reflective capabilities as well as the ability to empathise and tone down power asymmetries that can hamper genuine dialogue.…”
Section: Foundations Of Authentic Leadership Trust and Commitmentmentioning
confidence: 98%
“…The competencies, often called emotional intelligence (EI), were recognised as leadership competence and are now believed to be a key project management competence (Dulewicz and Higgs, 2000;Müller and Turner, 2007) through a number of recent studies in PM across industry sectors (Turner et al, 2009) and in specific sectors such as defence (Turner and Lloyd-Walker, 2008) and construction (Dainty et al, 2004(Dainty et al, , 2005. EI often encompasses self-reflective capabilities as well as the ability to empathise and tone down power asymmetries that can hamper genuine dialogue.…”
Section: Foundations Of Authentic Leadership Trust and Commitmentmentioning
confidence: 98%
“…The behavioural component of the RBP taxonomy provides details of the specific skills, knowledge, attributes and experience (SKAE) necessary to effectively participate in an alliance from entry level through to alliance project leadership roles. SKAEs identified by Walker and Lloyd-Walker (2011) for alliancing are supported by others (Dulaimi, Ling, Ofori and De Silva, 2002;Baiden, Price and Dainty, 2003;Dainty, Cheng and Moore, 2005;Dainty, Qin and Carrillo, 2005;Baiden, Price and Dainty, 2006;Ibrahim, Costello and Wilkinson, 2013) who have studied a range of high-level project team collaboration situations. Clearly attitude is a highly relevant characteristic.…”
Section: Discussion About the Rationale For Choosing An Alliancementioning
confidence: 58%
“…According to the results they revealed, some of the variables are also found in the competency school of leadership, such as achievement orientation, analytical thinking, as well as impact and influence [72]. Dainty et al [73] found in another study that superior performing project managers demonstrate 11 generic leadership behaviors: customer service orientation, initiative, conceptual thinking, information seeking, achievement orientation, teamwork and cooperation, team leadership, analytical thinking, impact and influence, flexibility, and self-control [73]. Construction industry is conventional in nature and remains technology and project oriented.…”
Section: Leadership Behaviors In Constructionmentioning
confidence: 99%